MICRODISCECTOMY AND PERCUTANEOUS ENDOSCOPIC LUMBAR DISCECTOMY: A BRIEF COMPARATIVE REVIEW - Kacper Domisiewicz; Agnieszka Walczak; Magdalena Domisiewicz (International Journal of Innovative Technologies in Social Science, 2026)
Background: Microdiscectomy (MLD) has long been considered the standard surgical treatment for lumbar disc herniation. Percutaneous endoscopic lumbar discectomy (PELD) has emerged as a minimally invasive alternative aimed at reducing tissue trauma and improving early postoperative recovery. Despite increasing adoption of endoscopic techniques, the relative advantages and limitations of these approaches remain debated [1–4]. Objective: This narrative review provides a concise comparison of microdiscectomy and percutaneous endoscopic lumbar discectomy based on available randomized controlled trials and comparative studies, with emphasis on clinical outcomes, perioperative recovery, complications, and practical considerations. Methods: A focused narrative review of randomized controlled trials and comparative clinical studies evaluating MLD and PELD was performed. Outcomes of interest included pain relief, functional improvement, perioperative recovery, complication profiles, and technical considerations. Results: Available evidence demonstrates comparable clinical outcomes between MLD and PELD in terms of pain relief and functional improvement [1–4]. PELD is associated with reduced postoperative tissue injury, less early postoperative back pain, and faster recovery [2,4,5]. Complication rates are similar overall, although the type of complications differs between techniques [1,4,14]. Outcomes after PELD are more strongly influenced by surgeon experience [19]. Conclusion: MLD and PELD provide comparable effectiveness in the treatment of lumbar disc herniation. PELD offers advantages in early recovery, while MLD remains a reliable and widely applicable technique. These procedures should be regarded as complementary.